Thiol–Gelatin–Norbornene Bioink for Laser‐Based High‐Definition Bioprinting. Issue 15 (26th July 2019) - Dobos, Agnes; Van Hoorick, Jasper; Steiger, Wolfgang; Gruber, Peter; Markovic, Marica; Andriotis, Orestis G.; Rohatschek, Andreas; Dubruel, Peter; Thurner, Philipp J.; Van Vlierberghe, Sandra; Baudis, Stefan; Ovsianikov, Aleksandr
Abstract: Two‐photon polymerization (2PP) is a lithography‐based 3D printing method allowing the fabrication of 3D structures with sub‐micrometer resolution. This work focuses on the characterization of gelatin–norbornene (Gel–NB) bioinks which enables the embedding of cells via 2PP. The high reactivity of the thiol‐ene system allows 2PP processing of cell‐containing materials at remarkably high scanning speeds (1000 mm s −1 ) placing this technology in the domain of bioprinting. Atomic force microscopy results demonstrate that the indentation moduli of the produced hydrogel constructs can be adjusted in the 0.2–0.7 kPa range by controlling the 2PP processing parameters. Using this approach gradient 3D constructs are produced and the morphology of the embedded cells is observed in the course of 3 weeks. Furthermore, it is possible to tune the enzymatic degradation of the crosslinked bioink by varying the applied laser power. The 3D printed Gel–NB hydrogel constructs show exceptional biocompatibility, supported cell adhesion, and migration. Furthermore, cells maintain their proliferation capacity demonstrated by Ki‐67 immunostaining. Moreover, the results demonstrate that direct embedding of cells provides uniform distribution and high cell loading independently of the pore size of the scaffold. The investigated photosensitive bioink enables high‐definition bioprinting of well‐defined constructs for long‐term cell culture studies. Abstract : Thiol‐ene photoclick chemistry allows rapid high‐definition bioprinting of cell‐containing constructs. Gelatin–norbornene bioinks crosslinked by dithiothreitol and a biocompatible 2‐photoninitiator are characterized by structure swelling, degradation, and stiffness studies. The biocompatibility of the system is established by direct encapsulation of fibroblast cells which show increased survival for up to 5 weeks.